A new method for the assessment of the surface topography of NiTi rotary instruments. (28th October 2016) - Ferreira, F.; Barbosa, I.; Scelza, P.; Russano, D.; Neff, J.; Montagnana, M.; Zaccaro Scelza, M.
Abstract: Aim: To describe a new method for the assessment of nanoscale alterations in the surface topography of nickel–titanium endodontic instruments using a high‐resolution optical method and to verify the accuracy of the technique. Methodology: Noncontact three‐dimensional optical profilometry was used to evaluate defects on a size 25, .08 taper reciprocating instrument (WaveOne ® ), which was subjected to a cyclic fatigue test in a simulated root canal in a clear resin block. For the investigation, an original procedure was established for the analysis of similar areas located 3 mm from the tip of the instrument before and after canal preparation to enable the repeatability and reproducibility of the measurements with precision. All observations and analysis were taken in areas measuring 210 × 210 μm provided by the software of the equipment. Results: The three‐dimensional high‐resolution image analysis showed clear alterations in the surface topography of the examined cutting blade and flute of the instrument, before and after use, with the presence of surface irregularities such as deformations, debris, grooves, cracks, steps and microcavities. Conclusions: Optical profilometry provided accurate qualitative nanoscale evaluation of similar surfaces before and after the fatigue test. The stability and repeatability of the technique enables a more comprehensive understanding of the effects of wear on the surface of endodontic instruments.